β-cyclocitral as a cross-species mediator of abiotic stress signaling: insights and future directions toward crop improvement - Lachica, Grace; Basnet, Prakash; Laurena, Antonio; Ocampo, Eureka Teresa; Choi, Ik-Young (Frontiers in Plant Science, 2026)
Abiotic stresses such as drought, salinity, heavy-metal toxicity, and photooxidative damage severely constrain global crop productivity, a challenge intensified by ongoing climate change. The apocarotenoid β-cyclocitral (β-CC), produced via both carotenoid cleavage dioxygenase (CCD)-mediated and reactive oxygen species (ROS)-driven oxidation, has emerged as a conserved signaling molecule that enhances plant adaptation to environmental stress. β-CC mitigates oxidative damage, promotes root system remodeling, and activates detoxification pathways through ABA-independent mechanisms involving the transcriptional regulators MBS1 and SCL14. Its oxidized derivative, β-cyclocitric acid (β-CCA), extends this signaling framework by modulating the cyclin kinase inhibitor SMR5 and the cytochrome P450 gene CYP81D11, thereby strengthening photosynthetic capacity, ROS control, and developmental reprogramming under drought and high-light stress. Beyond vegetative responses, β-CC also enhances seed vigor and longevity through apocarotenoid-dependent regulation of antioxidant activity and aquaporin expression. Comparative studies across Arabidopsis, rice, tomato, quinoa, and peach reveal both conserved and species-specific outcomes, underscoring the versatility of β-CC/β-CCA signaling. The broad occurrence of these apocarotenoids highlights their potential as natural biostimulants and molecular tools for improving stress resilience in crops. Although direct studies in soybean remain limited, conserved orthologs and signaling components point to promising translational opportunities. Future research should clarify the dynamics of β-CC and β-CCA accumulation, validate conserved gene networks such as MBS1/SCL14/CYP81D11, and develop stable, field-compatible delivery systems. Integrating mechanistic and physiological insights from model species will accelerate the application of β-CC-based strategies for climate-resilient agriculture.